Do Rewards Motivate or Else : A Study of the Public and Private Sector Employees - Jain, Samta; Mehta, Namrata (SFIMAR Research Review, 2019)
â€˜In an organization Rewards can help create the right employee - management team environment. Also create an atmosphere that is encouraging and favorable to achieving the contributions and efforts an organization need. But sometimes, same rewards and recognition when awarded to the employees who give finishing touch in his/her job, creates an environment of chaos among employees who really worked very hard. It is through the organization’s reward system that good employees are attracted to the organization; they decide to stay within the organization and then consciously decide to perform well. Employees perform at the level at which the organization rewards them. People continue to do what they have been rewarded for doing. This is a form of positive reinforcement. Yet managers must know what rewards mean the most to which employees in order to be the most effective. This study aims at studying the pros and cons of rewards when not given to the right person. A detailed knowledge of the topic is gained by secondary research backed by primary data.